Structural Factors Affecting Police Performance: An Evidence from Pakistan - Khan, Asim Muneeb; Aziz, Latafat; Shahzad, Muhammad Nadir; Abbas, Zaheer; Bhutta, Mazhar Hussain (International Journal of Psychosocial Rehabilitation, 2020)
Various factors indicate the performance of police department such as policing style, resources available with the police department, strength&geographical area covered by police stations, thepromotion and recruitment system, accountability, duty hours of police personnel, nature of duty etc. These factors are actual barriers for the better performance of police. The present research work was interested to highlight the structural barriers that affect the police performance. We collected data through cross-sectional interviews by interviewing 502 respondents that includedaffectees (247)and non-affectees (255) in Islamabad and Rawalpindi cities of Pakistan. It was revealed through regression analysis that major indicators are technical soundness of police and support from the government.It was concluded that theeffective policing strategies such as community policing and the enhancement of resources available with the police department have a strong association with their effective performance. We also considered other factorssuch as involvement of politics that affects the overall performance of police department. For rapid development and performance of police, there is a dire need of pumping up of new hope and thestructure needs fulfilment and depoliticizing the police department.